Simulation of Assembly Line Balancing in Automotive Component Manufacturing - Muthanna , Jamil; Noraini, Mohd Razali (IOP Publishing, 2016)
This study focuses on the simulation of assembly line balancing in an automotive component in a vendor manufacturing company. A mixed-model assembly line of charcoal canister product that is used in an engine system as fuel's vapour filter was observed and found that the current production rate of the line does not achieve customer demand even though the company practices buffer stock for two days in advance. This study was carried out by performing detailed process flow and time studies along the line. To set up a model of the line by simulation, real data was taken from a factory floor and tested for distribution fit. The data gathered was then transformed into a simulation model. After verification of the model by comparing it with the actual system, it was found that the current line efficiency is not at its optimum condition due to blockage and idle time. Various what-if analysis were applied to eliminate the cause. Proposed layout shows that the line is balanced by adding buffer to avoid the blockage. Whereas, manpower is added the stations to reduce process time therefore reducing idling time. The simulation study was carried out using ProModel software.